A fast numerical method for optimal coordination of overcurrent relays in the presence of transient fault current. Issue 2 (13th November 2017) - Mohammadi Chabanloo, Reza; Mohammadzadeh, Nima
Abstract : In the past, many studies have been conducted on the optimal coordination of overcurrent (OC) relays. In these studies, the short‐circuit current flowing through the relays is considered as fixed. In a real power network, however, for various reasons including the transient behaviour of synchronous generators, the short‐circuit current that flows through the relays varies with time. Therefore, the relay settings, which are obtained with the assumption of a constant, short‐circuit current, may cause miss‐coordination under real conditions. In this study, a numerical method based on the dynamic model of the relay is presented using linear programming (LP) to take account of the effect of transient currents on the coordination of OC relays. The method can be used as a fast numerical algorithm in the computing software to obtain accurate settings for OC relays in the presence of various transient fault currents in the network. Furthermore, the combination of LP with a genetic algorithm is used to incorporate the current setting of the relays in the transient coordination algorithm to achieve a better operating time for the relays. The results show the effectiveness of the proposed algorithms as compared with the previously presented method.